Hey Google: A thematic analysis of Twitter users' comments on the privacy of AI devices in the home. Issue 4 (1st December 2021) - Riddell, Heather; Fenner, Christopher
The advancement of technology has been accompanied by the rise of data breaches and privacy concerns. The integration of artificial intelligence (AI)-based virtual assistants into society has led to smart homes that enable users to complete commands instantly. This project uses the diffusion of innovation theory to explain why consumers adopt the technology. A thematic analysis was conducted on Twitter news stories, and open coding showed a strong negative reaction to the stories, with users concluding that privacy was too essential to purchase a virtual assistant for their home. These findings have implications for the future rate of adoption of AI and virtual assistant technology.